Implicit and explicit personality theories of depressed patients. - García Galindo, José Teodoro; Muiños Martínez, Ruben; Ferrer García, Marta; Tous Ral, José María (Anales de Psicología / Annals of Psychology, 2013)
Implicit and explicit theories of depressive personality are compared. A list of adjectives was administered for hetero-evaluation to 400 participants, divided into four groups: depressed patients, general population, doctors, and nurses. Depressed patients were re-administered the list of adjectives for self-evaluation. A descriptive study was conducted using χ2 to discriminate the adjectives used between groups. Two ANOVAs were then performed to establish differences between groups from hetero-evaluation and to test the presence of differences between the hetero- and the self-evaluation. Results showed the existence of differences in the stereotype of the people with depression between the clinically depressed group, the group of doctors and the group of nurses but not evidence of stigma. However, the general group showed prejudiced beliefs in their perception of depressed people. Depressed patients showed a more positive hetero-evaluation of depressive personality than of their own self-evaluation.